FAKTORâ€“FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ULKUS DIABETIKA PADA PENDERITA DIABETES MELLITUS DI RSUD. DR. SOEDARSO DAN KLINIK KITAMURA PONTIANAK - Mitasari, Gity; Saleh, Ismael; Marlenywati, Marlenywati (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2014)
Background : People with diabetes mellitus have a 15-25% possibility to experience diabetic foot ulcer in their lifetime. They also have the potency for recurrence of 50-70% for 5 years. The number of diabetic foot ulcer cases at DR.SOEDARSO hospital Pontianak increased sharply each year. In 2011, the proportion of diabetic ulcers was 3,19%. In 2102, the cases raised to 5,08 %. In 2013, the cases continually increased to 5,41%. If not promptly treated, diabetic ulcers will lead to decay and result in amputation Objective : This study aimed at discovering the factors associated with the incidence of diabetic ulcers in patients with diabetes mellitus at Dr.Soedarso Hospital and Kitamura Clinic Pontianak. Methods : A case control design was carried out in this study. The samples were 74 respondentsconsisted of 37 case group and 37 control group. They were selected by using accidental sampling. Then, the data were statistically analyzed by using Chi square test. Result : The study revealed two findings. First, there were significant correlations of â‰¥8 years DM experience (p value = 0,19), previous ulcer history (p value = 0,000), exercise habit (p value = 0,000), medication adherence (p value = 0,010), smoke exposure (p value = 0,005), foot care (p value = 0,027) and foot ware usage (p value = 0,002). Second, there were no correlations of physical activity (p value = 0,352), dietary compliance (p value = 0,485), and age (p value = 0,485). Conclusions : As a result, either Dr. Soedarso Hospital or Kitamura Clinic should improve the education, information, and communication to the patients with diabetes mellitus. Also, people with DM require to exercise regularly, take regular treatment/medication, avoid smoke exposure, take foot care, and wear appropriate foot ware. These ways are expected to prevent from unwanted incidence and minimize the complication.Key words : duration of DM, ulcer history, Diabetes Mellitus, diabetic ulcer.